(untitled) - Fourie, Denise K. (Santa Barbara, Calif., 2009)
Designed to introduce LIS students to the ever-changing world of modern libraries and information centers, this text provides an important overview of libraries in the era of electronic information. It helps students build necessary core knowledge in such areas as electronic dissemination of information, the impact of the Internet on libraries, the changing responsibilities of library professionals, the new paradigm for evaluating information, and characteristics and functions of today's library personnel. Each chapter revolves around a pertinent topic: the history of libraries, job opportunities, collections, preparing materials for use, circulation, reference service, ethics in the information age, job search basics, and the Internet. References and relevant books, Web sites, and publications at the end of every chapter point to further resources
Keywords: Library science,Khoa học thư viện